2022
DOI: 10.3390/toxins14040276
|View full text |Cite
|
Sign up to set email alerts
|

Aflatoxin M1 in Raw Milk, Pasteurized Milk and Cottage Cheese Collected along Value Chain Actors from Three Regions of Ethiopia

Abstract: Milk is a highly nutritious and perfect natural food for humans. However, when lactating animals feed on Aflatoxin B1 (AFB1)-containing feed, the hydroxyl metabolite aflatoxin M1 (AFM1) contaminates the milk and dairy products. The objective of the current study was to assess the level of AFM1 in raw milk, normally pasteurized milk and Ethiopian cottage cheese collected from value chain actors (producers, collectors, processors and retailers). Cross-sectional study and simple random techniques were used to col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 35 publications
0
13
1
Order By: Relevance
“…Zebib, Abate [ 78 ] revealed that all milk samples collected among value chain actors were contaminated with AFM 1 . Aflatoxin M 1 is detectable within 12 h in milk after an animal consumes feed contaminated with AFB 1 [ 79 ].…”
Section: Possible Sources Of Mycotoxin Exposure To Humans and Animalsmentioning
confidence: 99%
See 2 more Smart Citations
“…Zebib, Abate [ 78 ] revealed that all milk samples collected among value chain actors were contaminated with AFM 1 . Aflatoxin M 1 is detectable within 12 h in milk after an animal consumes feed contaminated with AFB 1 [ 79 ].…”
Section: Possible Sources Of Mycotoxin Exposure To Humans and Animalsmentioning
confidence: 99%
“…The increasing consumption of animal products such as dairy, from different animal species, emphasises the need for carryover effect data from these animals as well, to ensure food safety. In Ethiopia, for example, all milk samples were reportedly contaminated with AFM 1 in varying concentrations [ 78 ]. There is a need to extend AF carryover surveillance to other mycotoxins and precursor compounds such as sterigmacystein and minor metabolites such as aflatoxicol.…”
Section: Possible Sources Of Mycotoxin Exposure To Humans and Animalsmentioning
confidence: 99%
See 1 more Smart Citation
“…Successive studies from Pakistan showed a significant incidence of raw milk contamination with AFM 1 in both summer (36%, 19%) and winter season (40%, 29%) [14,48]. Studies from countries whose climatic and geographical features contribute to the increased incidence of AFM 1 (> 50 ng/kg) in milk are Pakistan 53% [15], India 44% [49], Bangladesh 70% [50] and 23.8% [51], South Africa 81% [52], Ecuador 59.3% [53], and Ethiopia 62.5% [54]. The incidence of AFM 1 in milk in countries whose legislation prescribes an MRL of 500 ng/kg showed an incidence above 500 ng/kg were Brazil 38% [55], Pakistan 69% and 90.9% [56,57], and Ethiopia 21.9% [54].…”
Section: Occurrence Of Afm 1 In Milkmentioning
confidence: 99%
“…5,6 The United States Food and Drug Administration has set the allowable detectable amount of AFB1 at 20 ppb (μg mL −1 ), and the European Union has established a maximum allowable detection limit of 6.4 nM for AFB1 in cereals and their products. 7,8 Therefore, there is an urgent need to develop a rapid, simple, and sensitive method for accurately quantifying AFB1 and warning against food contamination.…”
Section: ■ Introductionmentioning
confidence: 99%